EXPLORING THE IMPLEMENTATION OF GIMKIT AS A FORMATIVE ASSESSMENT TOOL IN ENGLISH LANGUAGE LEARNING: PRACTICE AND EXPERIENCE - Nur Rahman, Taufiq; Anam, Syafi'ul (Journal of English Education and Linguistics, 2024)
This study aims to find out how teachers implement the concept of gamification with the Gimkit platform and students' experiences of using the Gimkit platform as a formative assessment tool in English language learning. This research was conducted in a high school in Madiun, Indonesia. The research started from a case study where the researcher found that many students did not want to participate in formative assessment activities because they thought that the atmosphere during formative assessment with traditional methods would only make students afraid and unable to focus on the questions. Semi-structured interviews were conducted with 10 students and 1 English teacher to collect data, and the data obtained was analysed using thematic analysis. The findings of this study show that teachers have several reasons related to the use of Gimkit, the first is because of technological advances, and the utilisation of facilities, teachers also provide information related to how to implement the Gimkit platform from the initial stage to the assessment stage, teachers also tell how students react when implementing formative assessment using Gimkit which has a positive impact because students become more interested in the activity, feel relaxed when working, and students can learn new English vocabulary from Gimkit., the use of Gimkit was also considered easy by students both in terms of preparation and use during formative assessment, the use of Gimkit also had a positive influence on students because students felt that when using Gimkit they experienced increased motivation and gained new knowledge.